The Correlation Between Biological Markers and Prognosis in Thyroid Cancer - Rami Hajjar; Ciprian Duta; Ionut Flaviu Faur; Catalin Prodan-Barbulescu; Hadi Alhajjar; Stelian Pantea (Biomedicines)
Background: Thyroid cancer incidence is rising globally. Papillary thyroid carcinoma (PTC) is the most common subtype, usually with a favorable prognosis, while follicular, medullary, and anaplastic thyroid carcinomas carry higher risks. This study examines the relationship between biological markers—BRAF V600E mutation, thyroglobulin (Tg), and calcitonin—and thyroid cancer prognosis. Materials and Methods: This retrospective study included 395 thyroid cancer patients treated from 2010 to 2018 at the Emergency Clinical Hospital “Pius Brînzeu” in Timișoara. Patients were grouped by BRAF V600E mutation status (n = 178 with, n = 217 without). Preoperative Tg and calcitonin levels were measured, and survival rates were analyzed using Kaplan–Meier and Cox regression. Results: Patients with the BRAF V600E mutation were older, presented with advanced stages, and had higher Tg and calcitonin levels, correlating with tumor progression (e.g., Tg: 30.5 ng/mL in stage I vs. 62.0 ng/mL in stage IV). Lower biomarker levels (<30 ng/mL Tg, <15 pg/mL calcitonin) were associated with significantly better five-year survival rates (82.1% vs. 67.5%). Advanced stage, age, and elevated biomarkers independently predicted increased mortality risk. Conclusions: The BRAF V600E mutation is associated with more aggressive thyroid cancer and poorer outcomes. Tg and calcitonin are reliable prognostic markers, aiding in risk stratification and personalized treatment strategies to improve outcomes in thyroid cancer care.